Canvas or temple? Tattoo as representation of the teen’s body - Restrepo Tobón, Maria Victoria; Díaz et al., Luz (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The present investigation was carried out in order to understand the representation of the body that has some teenagers tattooed and non-tattooed of the 10th and 11th grade of the Educational Institution La Salle de Campoamor, Medellín city; Likewise, it was intended to expand the frame of reference regarding the way of seeing and understanding the practice of tattooing with the understanding of some of its dimensions such as size, shape, location, number of tattoos and tattooing; the changes that this one is experiencing and the importance that the tattoo can have for some of the adolescents as a means to express their identity and their emotions; similarly, we sought to explain the reasons why some teenagers do not get tattooed. From the research it was possible to conclude that there is no significant difference between the conception of the body that tattooed and non-tattooed adolescents interviewed have, given that both describe it as a temple, a sacred place; which they must take care of and respect. Finally, this allowed the adolescent to be analyzed from a more intimate, personal and particular perspective.